Analysis of Nurse Role Determinants in Patient Safety Implementation at Royal Prima Marelan Hospital Inpatients - Ricky Suryamin; Sri Lestari Nasution; Tri Suci (Journal La Medihealtico, 2024)
Patient safety incidents are still a significant problem at Royal Prima Medan Hospital, where various types of services have risks that threaten patient safety. This study aims to analyze the determinants of nurses' role in implementing patient safety in the Royal Prima Marelan Hospital Inpatient in 2023. This cross-sectional study examines the relationship between independent variables (risk factors) and dependent variables (effects) concerning nurses' roles in patient safety in home inpatient settings. This study included 51 Royal Prima Marelan Inpatient Hospital nurses who were Saturated Sampling. Research variables include the nurse's function, knowledge, attitudes, facilities, and work experience. Univariate, bivariate, and multivariate analyses are used in this research as statistics in determining the frequency distribution or proportion of independent and dependent variables. In implementing patient safety, nurses' roles are primarily good (64.7%), their knowledge is high (60.8%), their attitudes are positive (51.0%), their facilities are reasonable (60, 8%), and their work experience is mostly > three years (64.7%). Based on the analysis of patient safety implementation, knowledge, attitudes, facilities, and work experience all significantly impacted nurses' roles (p=0.008, 0.000, and 0.002, respectively). Hospital nurses have a good attitude toward implementing patient safety, especially if they get good training. Nurse length of service affects patient safety training frequency. More frequent training and better patient safety implementation are associated with longer nursing careers.